'Distress thermometer' in a hospice – supporting holistic assessment and a possible outcome measure. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Roth, Lucy; Jones, Sue; Hunt, Kimberley; Cochrane, Yvonne
Abstract : Background: The Holistic Assessment of Concerns (HAC) or 'Distress Thermometer' is a tool identified by the North of England Cancer Network to support the holistic assessment of patients across the network. It consists of a list of 45 possible concerns. The patient highlights any problems that have troubled them recently. They then identify the three most important concerns scoring each on a distress score from 0–10. Teesside Hospice Audit Group has been exploring ways of measuring patient outcomes for a number of years. This is becoming increasingly important as the Care Quality Commission and Commissioners demand more evidence of a patient centred and effective service. Aims: The HAC Tool was introduced at Teesside Hospice in 2010. The aims of its introduction were to improve our holistic care of patients by identifying what matters most to them and to provide evidence of benefit to patients of our management. Following introduction of the tool we reviewed its implementation in the Inpatient Unit (IPU) and Day Care at the hospice. We analysed 17 sets of Day Care notes and 20 sets of Inpatient notes to assess whether an initial and follow up tool was completed appropriately for each patient. The number and type of concerns elicited were identified and any change in score for each concern was calculated. The average improvement in score across all concerns was 1.5 in Day Care and 2.85 on IPU. Further results will be included in the poster. Conclusion: As a result of this review we demonstrated that our interventions benefit patients at Teesside Hospice. It gives us some good patient centred evidence that our work is effective. We found the HAC was easy to complete. We plan to continue to use the HAC at Teesside Hospice as part of our assessment and planning of each patient's care.